Application of Dynamic Compaction in Reclaimed Roads - Hamidi, Babak; Nikraz, Hamid; Varaksin, Serge (The Australian Geomechanics Society, 2012)
Pavement layers are systematically constructed as engineered fills with specified properties and criteria; however these well built layers may be underlain by loose saturated subgrades that, if not treated, may be subject to undesirable and damaging deformations. This may be especially true for roads that are constructed on reclaimed land. Dynamic Compaction is a ground improvement technique that can and has been effectively utilised for treating thick loose layers of saturated in situ or reclaimed granular soils. In this paper, the application of Dynamic Compaction for improving loose sub-grades will be discussed using three case studies. The case studies have been specifically selected in a manner to demonstrate the applicability of this technique to hydraulic fills and truck dumped fills, to very large projects such as the 900,000 m2 Abu Dhabi Corniche, to moderately large projects such as Marjan Island Main Road corridor and to relatively small sized projects such as the 10,000 m2 approach roads of Reem Island Causeway. The projects can be in undeveloped locations or in urban areas.